ANALISIS SEKTOR POTENSI UNGGULAN ANALISIS SEKTOR POTENSI UNGGULAN GUNA PERENCANAAN PEMBANGUNAN EKONOMI KOTA BANDUNG - Ahmad Rizani Rizani (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
This study aims to identify and determine the leading sectors in Bandung City to illustrate leading economics activities that can be developed in order to boost economics potential in Bandung City. The analysis tools used include Shift-Share, Location Quotient (LQ) and Growth Ratio Model (GRM) analyses. The results of the study show that: (1) shift-share analysis showed that the economy of Bandung City during the period 2010-2017 increased by Rp. 70,697,045.9 million. The increase in economic performance in Bandung City can be seen from 16 (sixteen) sectors of economic activity that are positive; (2) based on the Location Quotient (LQ) analysis, the leading sectors in Bandung City consisting of 13 (thirteen) sectors, i.e. water supply procurement; garbage, waste and recycling management; construction sector; retail and wholesale trade; car and motorcycle repair; transportation and warehousing sector; accommodation and food provision; information and communication sector; financial and insurance services sector; real estate sector; corporate services sector; government administration, defense and social security; education services sector; health services sector and social activities and other service sectors; (3) the analysis of the Growth Ratio Model (GRM) showed that the dominant sectors of growth and large contributions consist of the construction sector, transportation and warehousing sector, accommodation and food provision sector, information and communication sector, corporate services sector, education services sector, health services sector and social activities and other service sectors; (4) weighting results based on Shift-Share, Location Quotient (LQ) analysis, and Growth Ratio Model (GRM) showed that 5 (five) sectors based on the highest potential weighting results are the information and communication sector, retail and wholesale trade sectors , car and motorcycle repair, transportation and warehousing sector, accommodation and food provision sector and other service sectors.